2020
DOI: 10.1039/d0dt00797h
|View full text |Cite
|
Sign up to set email alerts
|

Green synthesis of Ag/TiO2composite coated porous vanadophosphates with enhanced visible-light photo-degradation and catalytic reduction performance for removing organic dyes

Abstract: The prepared Ag/VPO@TiO2 composites are used for photodegradation of MB under visible light and catalytic reduction of 4-NP molecules.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 82 publications
0
7
0
Order By: Relevance
“…The results of gel electrophoresis and melting curves show that the G31 performs a new intramolecular structure rather than G-quadruplex (Figures S1 and S2). 22,23 We further incubated G31 and CatG4 oligomer in K + solution to form specific secondary structure (probable G-triplex) and G-quadruplex, respectively. The fluorescence was determined after adding ThT and incubating for hours.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of gel electrophoresis and melting curves show that the G31 performs a new intramolecular structure rather than G-quadruplex (Figures S1 and S2). 22,23 We further incubated G31 and CatG4 oligomer in K + solution to form specific secondary structure (probable G-triplex) and G-quadruplex, respectively. The fluorescence was determined after adding ThT and incubating for hours.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…As far as we know, most G-triplex researches are focused on a 11-mer sequence (5′-GGTTGGTGTGG-3′) truncated from thrombin binding aptamer (TBA) quadruplex. 16,21,22,24 The melting temperature (Tm) of this observed G-triplex was about 33.5 °C in a buffer solution containing 70 mM K + , suggesting that the structure is instable at physiological temperatures. 16 Therefore, exploiting new G-rich sequences which can form stable G-triplex is desired.…”
mentioning
confidence: 96%
“…13,14 Moreover, recent studies observed typical positive and negative peaks in circular dichroism (CD) spectra with G-triplexes and found G-triplexes exhibited similar catalytic properties compared with G-quadruplexes. 15,16 Such similarities indicate that stable G-triplexes may be functional even under physiological conditions. However, it is difficult to find the sequences that form stable G-triplex structures since the T m of G-triplexes is significantly lower than that of Gquadruplexes.…”
mentioning
confidence: 98%
“…However, it is difficult to find the sequences that form stable G-triplex structures since the T m of G-triplexes is significantly lower than that of Gquadruplexes. 15 To the best of our knowledge, most of the studies on G-triplexes only focused on 11-mer-TBA (5′-GGTTGGTGTGG-3′) (T m = 33.5 °C), [10][11][12]15,16 TTAGGG repeats (T m = 55 °C), 17,18 and a recently discovered sequence (5′-TGGGTAGGGCGGG-3′) (T m = 60 °C). 19 Hence, studies on stable G-triplexes remain limited, and the functions and applications of G-triplexes need further exploration.…”
mentioning
confidence: 99%
“…[43][44][45] Compared with above noble metals, Ag is more earth-abundant and thus holds promise for more widespread use. It is established that Ag can improve the electron transfer rate of Ag/TiO 2 hybrid, [46,47] which is beneficial to its applications in photocatalysis (dye degradation, [48,49] H 2 evolution, [50,51] ) and supercapacitor. [52] However, the use of such hybrid in NRR has not been investigated before.In this work, we report on the development of Ag@TiO 2 for N 2 reduction electrocatalysis.…”
mentioning
confidence: 99%